2021
DOI: 10.1002/ctm2.541
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED; Combined rs‐fMRI study on brain functional imaging and mechanism of RAGE‐DAMPs of depression: Evidence from MDD patients to chronic stress‐induced depression models in cynomolgus monkeys and mice

Abstract: More and more evidence show that major depressive disorder (MDD) is closely related to inflammation caused by chronic stress, which seriously affects human physical and mental health. However, the inflammatory mechanism of depression and its effect on brain function have not been clarified. Based on resting‐state functional magnetic resonance imaging (rs‐fMRI), we investigated change of brain functional imaging and the inflammatory mechanism of damage‐related molecular patterns (DAMPs)—receptor of advanced gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…T1WI and T2WI strategies enable the visualization of brain anatomy, whereas quantitative indices such as DTI measurements and T2 values can provide quantitative sensitivity when attempting to detect injury to the nervous system and gauge the efficacy of neuroprotective interventions 30 . The T2 hyperintensity of the bilateral prefrontal cortex is associated with increases in inflammation, vascular permeabilization, myelin turnover, water content and the accumulation of by‐products of myelin and axonal breakdown 31,32 . ADC and FA values are key quantitative DTI parameters that are closely correlated with the pathogenesis of depression.…”
Section: Discussionmentioning
confidence: 99%
“…T1WI and T2WI strategies enable the visualization of brain anatomy, whereas quantitative indices such as DTI measurements and T2 values can provide quantitative sensitivity when attempting to detect injury to the nervous system and gauge the efficacy of neuroprotective interventions 30 . The T2 hyperintensity of the bilateral prefrontal cortex is associated with increases in inflammation, vascular permeabilization, myelin turnover, water content and the accumulation of by‐products of myelin and axonal breakdown 31,32 . ADC and FA values are key quantitative DTI parameters that are closely correlated with the pathogenesis of depression.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous experimental studies have shown that HMGB1 may induce depressive-like behavior through membrane receptors, such as TLR4 and RAGE ( Liu et al, 2019 ; Xie et al, 2021 ; Xu et al, 2020a ; Yan et al, 2021 ). Upon binding to the RAGE receptor on the cell surface, HMGB1 initiates two common downstream pathways in the cell.…”
Section: The Possible Mechanism Underlying Hmgb1-induced Depressionmentioning
confidence: 99%
“…Ds-HMGB1 (disulfide-HMGB1) and fr-HMGB (fully reduced HMGB) induce depressive behaviour by inducing neuronal inflammation in contrast with nonoxid-HMGB1 (non-oxidizable chemokine-HMGB) [115]. Knockdown or inhibition of RAGE, a receptor to which HMGB1 can bind, may counteract the effects of chronic stress and behaviours that are characteristic of depression [116]. According to Chen et al, acupuncture alleviates depressive behaviour by modulating hippocampal Iba-1 and HMGB1 expression in rats exposed to chronic limiting stress [117].…”
Section: Hmgb1 In Psychiatrymentioning
confidence: 99%